(untitled) (Educação e Pesquisa, 2023)
The aim was to identify if there are, in the faculty, differences in gender, race, and especially intersectionality between gender and race in the academic access to strictu sensu postgraduate programs in physical education, as well as to verify if the lines of research cover said themes. A quantitative survey was conducted among the professor and researchers from all Brazilian strictu sensu postgraduate programs in physical education, this was done through a previous search in data registered and made available by CAPES and, afterward, through websites of which program in order to identify gender, color of the skin and line of research. It was observed that 65.8% of the professor are white men, while a small percentage (0.52%) are black women. Lines and projects present little relation with race and gender issues. Moreover, it was verified that researchers that receive Research Productivity grants (hereby PQ) are mostly male, with white or yellow skin, and with academic production in the biomedicine field. In conclusion, it was found that the inequalities of gender and race are heavily present in the strictu sensu postgraduate programs in physical education and that themes concerning gender and race are scarce.